Combining ESPI with laser scanning for 3D characterization of racing tyres sections. (May 2018) - Pagliarulo, Vito; Farroni, Flavio; Ferraro, Pietro; Lanzotti, Antonio; Martorelli, Massimo; Memmolo, Pasquale; Speranza, Domenico; Timpone, Francesco
Highlights: The use of ESPI to investigate tyre's section is proposed. The study is applied to two different tyres. The approach allows to identify the different materials composing the tyre. Moreover 3D laser scanner is employed to get a complete 3D model of the tyres. The work opens a new front to retrieve the full 3D model that is of particular importance for the physical models describing the tyre thermal behavior, the tyre grip behavior and the tyre wear. Abstract: In this work is exploited the possibility to use two optical techniques and combining their measurements for the 3D characterization of different tyres with particular attention to the tyre's section. Electronic Speckle Pattern Interferometry (ESPI) and Laser Scanner (LS) based on principle of triangulation have been employed for investigating and studying the tyre's section and 3D shape respectively. As case studies two different racing tyres, Michelin S9H and Pirelli Diablo respectively, have been considered. The investigation has been focused at the aim to evaluate and measure the section's components in order to add to the 3D model obtained by Laser Scanning accurate information about the different layers along through the tyres sections. It is important to note that the assessment about the different layers along the section is a very difficult task to obtain by visual inspection or classical microscopy and even with the LS. Here we demonstrate that the different layers can be easily highlighted and identified by mean of the ESPI.